COUNSELING ON THE BENEFITS OF EARLY BREASTFEEDING INITIATION FOR NEWBORNS - zulfa, zulfatularifah11; Kinanatul Qomariyah, Kinanatul Qomariyah (LP4M STIKes Karsa Husada Garut, 2024)
Early initiation of breastfeeding (IMD) is an important intervention that takes place immediately after a baby is born, involving skin-to-skin contact between mother and baby and the first breast milk (colostrum) within the first hour of life. This study aimed to explore the benefits of IMD on the success of exclusive breastfeeding and enhancing the immune system of newborns, and identify challenges and implementation strategies in different regions. Through a literature review method, this study analyzed relevant studies to understand the impact of IMD on infant health and the sustainability of breastfeeding practices. The results showed that IMD plays a significant role in increasing the success of exclusive breastfeeding, reducing the risk of infection, and strengthening the infant's immune system through the provision of colostrum, which is rich in antibodies and growth factors. However, IMD implementation in many regions still faces challenges, including low public awareness, lack of training for health workers, and cultural barriers. To overcome these challenges, strategies are needed that involve increased education, intensive training for health workers, and strong policy support. In conclusion, IMD is a critical first step for maternal and infant health, but further efforts are needed to ensure its optimal implementation in all regions.